The Influence of Destination Image and Price on Tourist Satisfaction - Devy Widya Apriandi; Rika Akana (STIESA Press, 2024)
This study aims to analyze the influence of destination image and price on tourist satisfaction at Floating Market Lembang, a popular tourist destination in Bandung known for its unique concept of a floating market, natural atmosphere, and various attractions and facilities. In this study, destination image refers to tourists' perceptions of the attractiveness, beauty, and facilities of the destination, while price relates to tourists' perceptions of the price appropriateness in comparison to the quality of services received. The research method used is quantitative, with data collected through questionnaires distributed to tourists who have visited Floating Market Lembang. The data analysis technique employed is multiple linear regression to determine the extent to which destination image and price variables influence tourist satisfaction. The results show that destination image and price significantly affect tourist satisfaction. Destination image has a greater positive impact compared to price. This indicates that tourists' perceptions of the quality and attractiveness of the destination play a crucial role in determining their satisfaction levels. In conclusion, Floating Market Lembang management should continuously enhance the destination's image and ensure that the prices offered are in line with the quality of services provided to increase tourist satisfaction.